CD19 and BAFF‐R can signal to promote B‐cell survival in the absence of Syk. (28th January 2015) - Hobeika, Elias; Levit‐Zerdoun, Ella; Anastasopoulou, Vasiliki; Pohlmeyer, Roland; Altmeier, Simon; Alsadeq, Ameera; Dobenecker, Marc‐Werner; Pelanda, Roberta; Reth, Michael
Abstract The development and function of B lymphocytes is regulated by numerous signaling pathways, some emanating from the B‐cell antigen receptor (BCR). The spleen tyrosine kinase (Syk) plays a central role in the activation of the BCR, but less is known about its contribution to the survival and maintenance of mature B cells. We generated mice with an inducible and B‐cell‐specific deletion of the Syk gene and found that a considerable fraction of mature Syk‐negative B cells can survive in the periphery for an extended time. Syk‐negative B cells are defective in BCR, RP105 and CD38 signaling but still respond to an IL‐4, anti‐CD40, CpG or LPS stimulus. Our in vivo experiments show that Syk‐deficient B cells require BAFF receptor and CD19/PI3K signaling for their long‐term survival. These studies also shed a new light on the signals regulating the maintenance of the normal mature murine B‐cell pool.